The Amazon basin as a moisture source for an Atlantic Walker-type Circulation - Hierro, Rodrigo Federico (2019)
The Amazon basin constitutes the most developed rainforest in the world, accounting for 15-20% of the global freshwater input into the oceans. The low level flow over this region is climatologically dominated by the Atlantic anticycslone and the trade winds. This yields an incoming oceanic moist air to the continent from the East, which is forced to lift up over the Andes range at the West. The confluence of the entrance of humidity, heat, evaporation and strong rainfall results in an accumulation of water vapor in this region. There is a statistically significant surplus of humidity over land as compared to over ocean (the largest difference is found during austral summer). This turns the Amazon basin into one of the most important heat sources for the tropical atmosphere, feeding a global pattern like the Atlantic Walker-type circulation, where the ascent stage is not over ocean but over land. The Global Positioning System radio occultation data show to be an excellent tool to observe the accumulated water vapor above the Amazon basin.